Inferential Costs of Trait Centrality in Impression Formation: Organization in Memory and Misremembering - Nunes, Ludmila D.; Garcia-Marques, Leonel; Ferreira, Mário B.; Ramos, Tânia (Frontiers in Psychology, 2017)
An extension of the DRM paradigm was used to study the impact of central traits (Asch, 1946) in impression formation. Traits corresponding to the four clusters of the implicit theory of personality – intellectual, positive and negative; and social, positive and negative (Rosenberg, Nelson, & Vivekananthan, 1968) - were used to develop lists containing several traits of one cluster and one central trait prototypical of the opposite cluster. Participants engaging in impression formation relative to participants engaging in memorization not only produced higher levels of false memories corresponding to the same cluster of the list traits but, under response time pressure at retrieval, also produced more false memories of the cluster corresponding to the central trait. We argue that the importance of central traits stems from their ability to activate their corresponding semantic space within a specialized associative memory structure underlying the implicit theory of personality.